An analytic model to investigate the demand propagation in EOI supply networks. (2017) - Montanari, Roberto; Bottani, Eleonora
This paper builds upon the study by Montanari et al. (2015). These authors presented a probabilistic approach, named M.DPA.eoq, to predict the demand seen by an upper-tier echelon (e.g., a distribution centre) of a supply network, serving several lower-tier echelons (e.g., retail stores) operating according to an economic order quantity (EOQ) policy. In this paper, we investigate the case of the economic order interval (EOI) policy and thus formulate the Montanari demand probabilistic approach in the EOI scenario (M.DPA.eoi) framework. Although its analytic formulation is not so simple, the M.DPA.eoi is quite easy to understand and can be implemented without difficulties in general-purpose software, such as Microsoft Excel™. Therefore, it is expected to be directly exploited by supply network managers, to estimate the distribution of the demand the upper-tier echelon will face in a defined network structure. The model is tested on four scenarios, with different network structures and different behaviours of the lower-tier echelons.